Systematics of the combtooth blenny clade Omobranchus (Blenniidae: Omobranchini), with notes on early life history stages - Gibbs, Sean; Hundt, Peter J.; Nelson, Andrea; Egan, Joshua P.; Tongnunui, Prasert; Simons, Andrew M. (Zootaxa, 2018)
The combtooth blenny (Blenniidae) genus Omobranchus contains small, cryptobenthic fishes common to nearshore habitats throughout the Indo-West Pacific. Recent molecular systematic studies have resolved Omobranchus as monophyletic but little research has been done to resolve species-level relationships. Herein, phylogenetic analyses of one mitochondrial (CO1) and four nuclear (ENC1, myh6, sreb2, and tbr1) genes provide evidence for the monophyly of Omobranchus and support for the elongatus and banditus species group. Sampling of multiple individuals from widespread species (O. ferox, O. punctatus, and O. elongatus) suggested that the Thai-Malay Peninsula is a phylogeographic break that may be a historic barrier to gene flow. Additionally, common meristics and other morphological characters are used to describe an early life history stage of O. ferox and O. punctatus.